A Dinuclear Persulfide‐Bridged Ruthenium Compound is a Hypoxia‐Selective Hydrogen Sulfide (H2S) Donor. Issue 3 (16th November 2020) - Woods, Joshua J.; Wilson, Justin J.
Abstract: Hydrogen sulfide (H2 S) is a gaseous molecule that has received attention for its role in biological processes and therapeutic potential in diseases, such as ischemic reperfusion injury. Despite its clinical relevance, delivery of H2 S to biological systems is hampered by its toxicity at high concentrations. Herein, we report the first metal‐based H2 S donor that delivers this gas selectively to hypoxic cells. We further show that H2 S release from this compound protects H9c2 rat cardiomyoblasts from an in vitro model of ischemic reperfusion injury. These results validate the utility of redox‐activated metal complexes as hypoxia‐selective H2 S‐releasing agents for use as tools to study the role of this gaseous molecule in complex biological systems. Abstract : Exploration of the biological activity of a dinuclear persulfide‐bridged ruthenium complex identified an exciting class of compounds for delivery of H2 S to hypoxic cells (see picture). H2 S release from this redox‐activated metal complex protected H9c2 rat cardiomyoblasts from an in vitro model of ischemic reperfusion injury.